Effect of client centred therapy and reality therapy in fostering HIV voluntary counselling and testing among secondary school students in Oyo-State, Nigeria (2009)
Voluntary HIV testing is being currently adjudged as one of the major ways by which one's HIV status can be ascertained so as to either maintain a negative status or seek health care services in case one is positive. However, submitting oneself to HIV test voluntarily has become difficult even among the elites due to various reasons, ranging from fear of being tested positive to HIV, misinformation, stigmatisation and discrimination. Counselling with an appropriate method remained the only way to achieve this. The objective of this study is to investigate the effectiveness of client centred and .reality therapies in the improvement of VCT among secondary school students. the pre-test, post-test, control group, quasi-experimental design with 3x2x2 factorial matrix was used. Stratified simple random sampling was adopted in selecting 120 participants from three public secondary schools in Iseyin. Participants were subjected to six weeks of training in client centred therapy and reality therapy while participants in the control group received no training. Voluntary and counselling testing scale was used to collect data from the respondents. Data obtained were analysed using analysis of covariance (ANCOVA). Findings revealed that the students in the two experimental groups were significantly higher in their acceptance of HIV testing than those in the control group. This indicated that CCT and reality therapy were effective in fostering VCT.( F=22.46, df2,P<0.0 1). Reality therapy was however most effective in fostering VCT and therefore, clinical psychologist, social workers, counselling and health care providers could make use of it in solving HIV/VCT related problems.